1998
DOI: 10.1094/mpmi.1998.11.1.45
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Component System Plays an Important Role in the Root-Colonizing Ability of Pseudomonas fluorescens Strain WCS365

Abstract: We describe the characterization of a novel Tn5lacZ colonization mutant of the efficiently colonizing Pseudomonas fluorescens strain WCS365, mutant strain PCL1210, which is at least 300- to 1,000-fold impaired in colonization of the potato root tip after co-inoculation of potato stem cuttings with a 1:1 mixture of mutant and parental cells. Similarly, the mutant is also impaired in colonization of tomato, wheat, and radish, indicating that the gene involved plays a role in the ability of P. fluorescens WCS365 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 58 publications
3
100
0
Order By: Relevance
“…In line with this, it was shown that transposition of the catabolic transposon Tn4652 in nutrient-starved Pseudomonas putida (104) is triggered by environmental cues through a two-component system, ColR-ColS. This signal relay system was previously identified as an important root colonization factor in Pseudomonas fluorescens (49).…”
Section: Genes Involved In Transposition Andmentioning
confidence: 77%
“…In line with this, it was shown that transposition of the catabolic transposon Tn4652 in nutrient-starved Pseudomonas putida (104) is triggered by environmental cues through a two-component system, ColR-ColS. This signal relay system was previously identified as an important root colonization factor in Pseudomonas fluorescens (49).…”
Section: Genes Involved In Transposition Andmentioning
confidence: 77%
“…Motility was tested as described by Dekkers et al (5). Briefly, KB was diluted 20-fold, semisolidified with 0.3% agar (Select agar), and poured into petri dishes.…”
Section: Methodsmentioning
confidence: 99%
“…To measure motility, semisolid (0.35% agar) agar plates containing King B medium diluted 1:20 were used (4). Growth in competition in SSM was carried out as described by Dekkers et al (27).…”
Section: Methodsmentioning
confidence: 99%